Faith and Finance: How Religiosity Shapes Islamic Fintech Adoption in Indonesia - Yulfiswandi; Licca, Vellia; Hesniati (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2026)
Islamic Fintech has developed in Indonesia over the past few years. This study examines Indonesians’ perceptions and intentions of both Muslim and Non-Muslim respondents on Islamic Fintech. Primary data was gathered through an online survey from 252 participants, who were chosen based on a convenience sampling method. Nine hypotheses were formulated and tested using SEM-PLS. The results show that perceived ease of use, perceived usefulness, trust, subjective norms, and religiosity significantly influence the intention to adopt Islamic Fintech. Furthermore, the interaction between trust and subjective norms in shaping usage intention was found to be moderated by religiosity. These findings suggest that individuals with stronger religiosity align their trust and social influence with religious values when evaluating Islamic Fintech adoption. To gain deeper insights, a multi-group analysis was conducted by dividing respondents into low and high-religiosity groups. For low religiosity users, only perceived ease of use and trust significantly affect intention. For high religiosity users, only religiosity does not have a significant effect on intention to adopt. No significant moderating effects were found across groups. The study contributes to understanding user behavior in the context of Islamic Fintech and highlights the importance of religiosity in shaping adoption decisions within a diverse religious society. Practically, it suggests that Islamic Fintech providers should focus on user-friendly platforms, trust-building mechanisms, and targeted strategies that account for varying levels of religiosity.